Mapping social entrepreneurship in Germany: a quantitative analysis : working paper - Scheuerle, Thomas; Schmitz, Björn; Spiess-Knafl, Wolfgang; Schües, Rieke; Richter, Saskia (SSRN eLibrary, 2013)
In this paper we present data from a quantitative online survey among 244 social enterprises in Germany. Social entrepreneurship research is often criticized for a lack of quantitative approaches, partly due to a still missing consent on definition criteria. Therefore we depart from a discussion of definition criteria that are related to the major schools of thought in the field - earned income, innovativeness, and democratic governance - and of sampling techniques that have been applied in previous quantitative studies. Building on a bottom up sampling approach, we found for example that most social enterprises in our study are rather young and small in terms of income and employees. Nevertheless, there are also mature organizations considerably larger in size. We also found that social enterprises rely on a variety of income streams. The share of organizations with a formal advisory board in their governance structure was high for very young as well as for older organizations. Although most organizations have a regional scope, scaling endeavors were planned by most organizations. We discuss our results within the context of German welfare structures and provide some conclusions on the issue of quantitative studies of social entrepreneurship.